Efficacy of transcutaneous electrical nerve stimulation in the treatment of chronic pelvic pain - Sharma, Nidhi (J Midlife Health, 2017)
BACKGROUND: Chronic pelvic pain is prevalent in 2% of women population globally. The etiology is multifactorial. Even in the absence of pelvic pathology, there is a subgroup of women who do not respond to analgesic and anti-inflammatory therapy. Chronic pelvic pain can be inhibited by direct inhibition of impulses in the preganglionic afferent neuron by closing the hypothetical gate in the dorsal horn of the spinal cord. Transcutaneous electrical nerve stimulation (TENS) is based on the gate control theory of abolishing the painful stimuli by providing simultaneous inputs in larger myelinated nerve fibers. AIMS AND OBJECTIVES: This study was designed to assess the effectiveness and safety of TENS in idiopathic chronic pelvic pain. METHODS: It is a prospective, experimental study to evaluate the effectiveness of TENS versus placebo in reducing pain severity in chronic pelvic pain (G1 = 30, G2 = 32, G3 = 30, and G0 = 30). Patients with chronic pelvic pain due to benign lesions of genital tract, gastrointestinal, and renal disorders were excluded from the study after performing an ultrasound study of abdomen and pelvis. Ten treatment sessions (5 sessions/week) of 30 min were conducted. OBSERVATIONS AND RESULTS: There was a significant improvement in pain scores in TENS group as compared with control group, and two patients were completely pain free following TENS therapy. CONCLUSION: In women patients with idiopathic chronic pelvic pain, TENS can be a useful intervention. TENS units are safe, economical, and easily commercially available.